ANALISIS BEBAN KERJA MENTAL PADA DEPARTEMEN PRODUKSI DI PT. JAYA PRAKARSA MENGGUNAKAN METODE NASA-TLX - Rafif Ghanduur Refanza; Kusnadi (Industry Xplore, 2023)
PT. Jaya Prakarsa is a manufacturing company that focuses on making packaging. Every day there are many custom orders by customers which result in many differences in the production process. This causes employees to have additional mental pressure and can result in stress at work. This study aims to reduce employee stress by using the NASA-TLX method and provide improvement solutions based on that method. NASA-TLX is a method of measuring mental workload by taking a questionnaire approach that will be distributed to employees in the Production Department. The figure obtained from the calculation results is 65.4 which is in the high category. After making observations using the results of the questionnaire, it is known that the factors that influence work pressure are the lack of work facilities, the minimum rest time obtained by employees, and the least motivation to work. The suggestions for reducing mental workload include adding facilities in the work area, increasing rest time, and providing activities that increase motivation for workers.Keywords: NASA-TLX, Mental Workload